The Role of Annexin A1 in DNA Damage Response in Placental Cells: Impact on Gestational Diabetes Mellitus - Moreli, Jusciele Brogin; Santos, Mayk Ricardo dos [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Hebeda, Cristina Bichels; Farsky, Sandra Helena Poliselli; Bevilacqua, Estela; Oliani, Sonia Maria [UNESP] (MDPI, 2023)
The functions of annexin A1 (ANXA1), which is expressed on membranes and in cytoplasmic granules, have been fully described. Nonetheless, the role of this protein in protecting against DNA damage in the nucleus is still emerging and requires further investigation. Here, we investigated the involvement of ANXA1 in the DNA damage response in placental cells. Placenta was collected from ANXA1 knockout mice (AnxA1−/−) and pregnant women with gestational diabetes mellitus (GDM). The placental morphology and ANXA1 expression, which are related to the modulation of cellular response markers in the presence of DNA damage, were analyzed. The total area of AnxA1−/− placenta was smaller due to a reduced labyrinth zone, enhanced DNA damage, and impaired base excision repair (BER) enzymes, which resulted in the induction of apoptosis in the labyrinthine and junctional layers. The placentas of pregnant women with GDM showed reduced expression of AnxA1 in the villous compartment, increased DNA damage, apoptosis, and a reduction of enzymes involved in the BER pathway. Our translational data provide valuable insights into the possible involvement of ANXA1 in the response of placental cells to oxidative DNA damage and represent an advancement in investigations into the mechanisms involved in placental biology.
Keywords: annexin A1 knockout mice; apoptosis; base excision repair; high-risk pregnancy; oxidative stress